Terracotta figurines from the National and Military Museums in Sana’a, Yemen - Yaseen, Ghassan Taha; D. Shargabi, Dhekra (Blackwell Munksgaard, 2007)
Terracotta figurines have been recovered through archaeological excavation at six sites in Yemen (Fig. 1). These include Wadi al-Thayyilah (1), Ma’rib (2), Wadi al-Jauf (3), Hajar bin Humeid (4), Sabir Lahj (5) and al-Quraiyat (6). The figurines in the National and Military Museums were not, however, discovered during controlled excavations but were obtained as donations or by purchase. Most of them show similarities with those from excavated sites in Yemen or with material from controlled excavations elsewhere in the Arabian Peninsula (Fig. 2) such as Qaryat al-Fau (7), Dumat al-Jandal (8), Thaj (9), ed-Dur (10), Mleiha (11), Rumeilah (12), Qal’at al-Bahrain (13) and Failaka (ancient Ikaros) (14). Correlation with similar types found in excavations in Yemen and elsewhere in the Arabian Peninsula indicates that they date from the second millennium BC to the end of the second century AD. In the following study fifty-one terracotta figurines in the National Museum (nos 1–13, 16–33, 35, 38–45, 50, 52, 53, 56–60 and 63–65) and fourteen in the Military Museum (nos 14–15, 34, 36–37, 46–49, 51, 54–55 and 61–62) are presented. All the figurines presented here were handmade. Tools may have been used to incise the eyes, mouth, necklaces, nipples, navel and belly furrows. The thumb and forefinger were generally used to suggest the spinal column, rump, eye cavities, nose and breasts. In some cases the eyes, breasts and hair were made separately and then affixed to the clay (applique´). There is no evidence of moulding. The figurines ranged from 13.5 to 462.5 g in weight and from 3.8 to 16.1 cm in height. The most common colours were Pale Red 10R 7/4, 7/2, 7/3, 6/4, 6/3, 6/2, 2.5YR 7/2; and Light Red 10R 6/6, 7/6, 7/8, 6/8, 2.5YR 7/6 (see Table 1). The figurines have been classified into five groups and sub-groups as outlined below. Hardness was measured using the Mohs scale, and colour designations are given according to the Munsell Soil Colour Chart.